A Cross‐Sectional Study on Immunization Status of School Going Adolescents in Indore, Madhya Pradesh - Ghelani, Pulkit; Inamdar, Sameer; Inamdar, Savita (National Journal of Community Medicine, 2014)
Background: With the advent of a number of new vaccines in last decade and huge money invested in immunization program by Indian/International agencies, the results and outcome of these efforts needed to be studied and analyzed. School-age and adolescent age groups are still poorly covered areas in the field of immunization. Approach: To study exact impact of factors possibly affecting immunization coverage like gender bias against females, socio-economic status of family, maternal education and place of vaccination, this study was carried out in schools of Indore in 2000 school-going adolescents to determine vaccination coverage of candidates and awareness of the parents about various aspects of immunization. Results: Results suggested a statistically significant positive impact of socio-economic status (p <0.001) and maternal education (p <0.001) on the overall immunization coverage and didn’t report any gender bias against the female candidates in immunization. Study also suggested a poor awareness of parents about optional vaccines and adolescent immunization. Conclusion: It is high time that the government makes necessary attempts to give a special focus on adolescent immunization and if possible, incorporate the immunization program into the school health program and also run special campaigns to cover the existing deficits in the immunization coverage to create a realistic opportunity to fulfill the dream of making India free of these VPDs one day.